Analyzing ethnic and cultural materials : insights into ELT materials - Zakaria, Mohd. Hassan; Ridis Rinyod, Bernadine Dorin (2010)

(untitled)
Ethnic and cultural materials and English Language Teaching (ELT) materials are related especially in terms of the emphasis on cultural knowledge and skills as well as the language and critical thinking skills. This study intends to research on ethnic and cultural materials within the perspectives of English language materials design. Specifically, the objectives of the study are to investigate the relevance and implications of such materials to ELT materials. The materials were selected from the content of Ethnic Relations course as it contained rich ethnic and cultural elements. When examining such materials from the perspectives of English language materials design, three aspects are considered: learner factors, text factors and task factors. The instrument used for the study was a checklist derived from works by Contazzi and Jin (2001), Nunan (2001), Tomlinson (2001) and Banks (1990). Basically, the checklist consists of 25 items and it was divided into three parts, learner factors, text factors, and task factors. The materials were analyzed using the checklist according to the specified criteria and the data obtained were represented in the form of description, examples and evidence. In addition, lecturers’ perceptions on the materials were attained using a set of interview questions. The findings indicate that a) ethnic and cultural materials have positive impacts on students’ interest and motivation, b) such materials include useful cultural elements and are comprehensible to students, and c) the tasks given are relevant and meaningful. The study also proves that lecturers dealing with ethnic and cultural contents are aware of the benefits of using such materials for teaching language and culture as it can foster critical thinking and develop communicative competence. Thus, the use of ethnic and cultural materials has a direct and significant implication to English language teaching and learning if the same criteria were to be applied when selecting and using ELT materials.